The Effect of Natural Ventilation on Indoor Air Temperature and Relative Humidity in Traditional and Modern Iban Longhouse in Sri Aman, Sarawak - Chong, Joynna; Mohd Azuan Bin Zakaria (Recent Trends in Civil Engineering and Built Environment, 2021)
Iban Longhouse or “rumah panjai” is an Iban’s residential building that symbolize of Iban ethnics in Sarawak. Effect from modernization bring an improvement towards the uses of material and design building of Iban Longhouse. The aim of the study is to identify material properties of traditional and modern Iban Longhouse and to compare the indoor thermal performance of traditional and modern Iban Longhouse in tropical climate country under natural ventilation. The field measurement has been carried out in traditional and modern Iban Longhouse in Sri Aman, Sarawak for 3 days and observed in daytime (6:00 am to 6:00 pm) and night time (6:00 pm to 6:00 am). The investigation was measured with Thermo Recorder TR-72U for air temperature and relative humidity. Finding shows that, indoor temperature in traditional Iban Longhouse is hotter by 7.3 and 7.6°C air temperature difference compared to outdoor temperature during day. At night time, the indoor temperature almost at the same state by 1.3°C and 1.4°C compare outdoor temperature. Meanwhile, in modern Iban Longhouse, the indoor temperature is cooler by -2.5°C and -2.8°C air temperature difference compared to outdoor temperature during day. During night time, the indoor temperature is warmer by difference 7°C and 7.2°C compare to outdoor temperature. The findings of the study found that the built materials may affect the indoor thermal performance in the Iban Longhouse. This study will help to contribute towards the improvement and modernisation in term of building materials of Iban Longhouse in tropical climate as well as occupant’s well-being in future.